Contemporary Challenges for Sharia Financial Institutions to Increase Competitiveness and Product Innovation Perspective of Sharia Economic Law: Evidence in Indonesia - Fadli Daud Abdullah; Doli Witro; Misbahul Munir Makka; Muhamad Sadi Is; Syahid Mujahid Wiwaha (MILRev: Metro Islamic Law Review, 2024)
Globalisation and technological advancement present contemporary challenges for Indonesia's Sharia Financial Institutions (LKS) in maintaining competitiveness and innovating. This study examines these challenges, including the acceleration of financial technology (fintech), regulatory changes, and rising consumer expectations for inclusive and efficient services. LKS is required to continuously innovate and create products that meet the needs of a dynamic market while still following the principles of Sharia economic law. This research discusses how LKS integrates fintech and Islamic financial technology in their operations. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through a literature study and document analysis related to government regulations and policies regarding Sharia Financial Institutions. The literature study and document analysis also included laws and regulations related to Islamic finance, Islamic economic law regulations, academic articles (journals), and books that discuss product innovation and competitiveness challenges of Sharia Financial Institutions. This study found that regulations such as the Financial Services Authority Regulation (POJK) and the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) provide a legal basis to support such innovation. However, LKS still faces challenges such as competition with conventional financial institutions, regulatory changes, and technological disruption. To remain competitive, LKS must adjust innovations such as Sharia fintech and crowdfunding following Sharia principles. In addition, public education on Sharia products is also important to increase financial inclusion. Through innovations such as factoring, bespoke financing, and solutions for online businesses, LKS can improve efficiency and empower small businesses while contributing to sustainable economic growth.